Some Functional Relations of I-functions using Saigo Fractional Integral Operator - Thakur, Anjali; Jain, D.K; Jain, Renu (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In the present paper we seek to establish functional relations between digamma functions and I-functions by using Saigo fractional integral operator. This paper is extension of the paper of functional relations of I-function by using Riemann-Liouville & Weyl fracatinal integral operators and Erd—lyi-Kober fracational integral operators.